Determination and explanation of the pH-related critical fluoride concentration of pure titanium in acidic solutions using electrochemical methods. (10th July 2015) - Wang, Z.B.; Hu, H.X.; Zheng, Y.G.
Abstract: The critical fluoride concentrations for titanium were determined experimentally in acidic solutions at pH  = 1.0∼5.0 using open circuit potential measurements combined with potentiodynamic polarization tests. The results indicated that the dependence of the critical fluoride concentration on pH (∂ pF /∂ pH ) could be classified into two pH regions: ∂ pF /∂ pH  = −0.17 at region I ( pH  = 1.0∼2.5) and ∂ pF /∂ pH  = −0.78 at region II ( pH  = 3.0∼5.0), respectively. Electrochemical parameters for titanium in fluoride-containing acidic solutions were obtained by analyzing the polarization curves quantitatively. It was found that hydrogen evolution reaction controlled by charge transfer, and oxygen reduction reaction controlled by mass transfer dominated the cathodic reactions at Region I and Region II, respectively. The ∂ pF /∂ pH values were calculated using the obtained parameters and were in line with the experimental results. Based on the calculations, the different ∂ pF /∂ pH values between Region I and Region II were mainly determined by the anodic parameter, ∂lg Im /∂ pH, rather than the cathodic parameters. Accordingly, anodic reaction mechanisms were proposed considering the existence forms of the fluoride. They could be fully utilized to qualitatively explain the phenomenon of pH-related critical fluoride concentration.